Ethnobotanical Study of Traditional Medicinal Plants in Gindeberet District, Western Ethiopia - Yirga, Gidey; Zeraburk, Samuel (Mediterranean Journal of Social Sciences, 2011)
Ethiopia, is a country characterized by a wide range of climate and ecological conditions, possesses enormousdiversity of fauna and flora. Semi-structured interviewees, observation and guided field walks with informants were employed toobtain ethnobotanical data in Gindeberet district, western Ethiopia. A total of 120 informants (84 males and 36 females) wereselected purposefully from six sub districts. A total of 26 species of medicinal plants were collected and identified for treating 36human ailments. The medicinal plant preparations were administered through oral, dermal and nasal routes. Oral application (33preparations, 67.3%) was the highest and most commonly used route of application followed by dermal application (15preparations, 30.6%). The most commonly used plant parts for herbal preparations were leaves (28%) and roots (28%) followedby barks (14%) and fruits (14%). Gindeberet district is rich in its medicinal plant composition and the associated indigenousknowledge. Encouraging the local herbal medicinal practitioners to enhance the use of traditional medicine and licensing thework of the practitioners are recommended.